Application of the multivariate and univariate analyses to estimate the feed efficiency in beef cattle (Bioscience Journal, 2023)
This study aimed to compare the univariate analyses (relationship between dry matter intake (DMI) and average daily gain (ADG), Kleiber ratio, and residual feed intake) and multivariate analysis (bionutritional index [BNI]) to determine feed efficiency. Were used a total of 160 cattle (individual data) and the analyzed variables were dry matter intake, weight gain, and body weight of the animals. We used five methods to evaluate feed efficiency, the BNI, FE, corrected feeding efficiency (corFE), Kleiber ratio (KR), and residual feed intake (RFI).  Study 1 demonstrated that only the FE (p=0.0472) was significant, although the FE after the transformation of Box-Cox (corFE) (p=0.0642) showed a statistical trend. In studies 2, 3, and 5, we observed that BNI was the best biological efficiency indicator. In the study 4, we observed that the best indicators were FE (0.110; p=0.0281), corFE (0.380; p=0.0429), and RFI (0.465; p=0.0340) for the genders. However, corFE decreased the coefficient of variation in all studies. In conclusion, the use of the Box-Cox transformation is as efficient as the multivariate analysis in discriminating experimental groups (genetic groups, different levels of concentrate in the diet, and genders) concerning the other univariate analyzes.